A new companion to Renaissance drama - Kinney, Arthur F., 1933-; Hopper, Thomas Warren (Hoboken, NJ : Wiley Blackwell, 2017)
'This book provides an invaluable summary of past and present scholarship surrounding the most popular and influential literary form of its time. Original interpretations from leading scholars set the scene for important paths of future inquiry'--
Envisioning Early Performances and AudiencesActors and Oral/Aural Culture; Acting Styles, Training, Rehearsal; Celebrated Actors; Clowns and Clowning; Impersonating Women; References and Further Reading; Chapter 16 Playhouses ; Introduction; 1567; 1575-1578; 1587, 1594; 1598-1600; 1607, 1614; 1617, 1623, 1630; References; Chapter 17 Theatrical License and Censorship ; Origins; Competing Authorities; Protector and Regulator; The End of Elizabeth's Reign; James I; Caroline Anxieties; Closing the Theaters; Notes; References and Further Reading; Chapter 18 Playing Companies and Repertory ; Notes
Machine generated contents note: List of Illustrations x Notes on Contributors xi Acknowledgments xviii Introduction 1 Arthur F. Kinney and Thomas Warren Hopper Part I Context 9 1 The Politics of Renaissance England 11 Norman Jones 2 Continental Influences 21 Lawrence F. Rhu 3 Medieval and Reformation Roots 35 Raphael Falco 4 Popular Culture and the Early Modern Stage 51 Sophie Chiari and Francois Laroque 5 Multiculturalism and Early Modern Drama 65 Scott Oldenburg 6 London and Westminster 75 Ian W. Archer 7 Travel and Trade 88 William H. Sherman 8 The Theater and the Early Modern Culture of Debt 98 Amanda Bailey 9 Vagrancy 112 William C. Carroll 10 Domestic Life 125 Martin Ingram 11 Religious Persuasions, c.1580-c.1620 143 Lori Anne Ferrell 12 Science, Natural Philosophy, and New Philosophy in Early Modern England 154 Barbara H. Traister 13 Magic and Witchcraft 170 Deborah Willis 14 Antitheatricality: The Theater as Scourge 182 Leah S. Marcus Part II Theater History 193 15 Performance: Audiences, Actors, Stage Business 195 S. P. Cerasano 16 Playhouses 211 David Kathman 17 Theatrical License and Censorship 225 Richard Dutton 18 Playing Companies and Repertory 239 Roslyn L. Knutson 19 Rehearsal and Acting Practice 250 Don Weingust 20 Boy Companies and Private Theaters 268 Michael Shapiro 21 Women's Involvement in Theatrical Production 282 Natasha Korda 22'To travayle amongst our frendes': Touring 296 Peter H. Greenfield 23 Progresses and Court Entertainments 309 R. Malcolm Smuts 24'What revels are in hand?' Performances in the Great Households 322 Suzanne Westfall 25 Civic Drama 337 Lawrence Manley Part III Genres 355 26 Masque 357 David Lindley 27 The History Play: Shakespeare and Beyond 371 Brian Walsh 28 Domestic Tragedy: Private Life on the Public Stage 388 Lena Cowen Orlin 29 Revenge Tragedy 403 Marissa Greenberg 30 Romance and Tragicomedy 417 Jane Hwang Degenhardt and Cyrus Mulready Part IV Critical Approaches 441 31 Sexuality and Queerness on the Early Modern Stage 443 Valerie Billing 32 Gendering the Stage 456 Alison Findlay 33 Race and Early Modern Drama 474 Mary Floyd?-Wilson 34 Staging Disability in Renaissance Drama 487 David Houston Wood 35 Space and Place 501 Adam Zucker 36 The Matter of Wit and the Early Modern Stage 513 Ian Munro 37 Materialisms 529 Elizabeth Williamson Part V Playwrights, Publishers, and Textual Studies 543 38 The Transmission of an English Renaissance Play?]Text 545 Grace Ioppolo 39 Publishers of Drama 560 Tara L. Lyons 40 Sidney, Cary, Cavendish: Playwrights of the Printed Page and a Future Stage 576 Lara Dodds and Margaret Ferguson 41 Nonprofessional Playwrights 598 Matteo Pangallo Index 612.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 25, 2017).
Keywords: 1500-1699; English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism; English drama -- 17th century -- History and criticism; Renaissance -- England; LITERARY CRITICISM / Drama; English drama; English drama -- Early modern and Elizabethan; Renaissance; England; Criticism, interpretation, etc; Electronic books